2017
DOI: 10.1159/000456719
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy with Ologen versus Mitomycin C in Juvenile Open-Angle Glaucoma: A 1-Year Study

Abstract: Background: We assessed bleb morphology and the intraocular pressure (IOP)-lowering effect of trabeculectomy with ologen compared to mitomycin C (MMC) in juvenile open-angle glaucoma (JOAG). Methods: This is a prospective interventional comparative study conducted on 40 eyes (20 patients) with medically uncontrolled JOAG, randomly operating one eye for trabeculectomy with ologen (group A: 20 eyes) and the other with MMC (group B: 20 eyes). IOP measurement, SITA standard perimetry, and spectral domain optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
(22 reference statements)
0
10
1
Order By: Relevance
“…These results are different to findings obtained by El‐Sayyad et al. () who demonstrated with AS‐OCT that OLO totally degraded in 100% of the eyes at 6 months. However, the investigators in this study assessed effects of OLO implant in juvenile glaucoma eyes which exhibit exaggerated healing reaction.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are different to findings obtained by El‐Sayyad et al. () who demonstrated with AS‐OCT that OLO totally degraded in 100% of the eyes at 6 months. However, the investigators in this study assessed effects of OLO implant in juvenile glaucoma eyes which exhibit exaggerated healing reaction.…”
Section: Discussioncontrasting
confidence: 99%
“…In this meta-analysis, one study was about juvenile open-angle glaucoma (JOAG), the results showed that Ologen resulted in a lower long-term postoperative IOP, a better bleb morphology, and fewer complications [29] . Another was about congenital glaucoma showed that Ologen had equally effective results as MMC, and Ologen implantation is safe and has low incidences of complications [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were excluded because they didn't compare the effect of Ologen implant and MMC or they were not prospective studies. After assessing the full text of the potentially 30 relevant articles, 15 RCTs were enligible for our inclusion criteria and finally to be included in this meta-analysis [22,[25][26][27][28][29][30][31][34][35][36][37][38][39][40] . The exclusion reasons were as follow: one was from the same patient group, and one compared the outcomes of trabeculectomy with or without an Ologen implant, seven were not comparative studies, five compared phacotrabeculectomy with Ologen implant and MMC, one was about secondary glaucomas trabeculectomy with following failed trabeculectomy with MMC.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9 However, two recently reported clinical trials of collagen matrix and MMC for trabeculectomy in patients with primary open angle glaucoma (POAG) found no difference in the success rate between the two anti-fibrotic agents after 12 months of follow-up. 10,11…”
Section: Introductionmentioning
confidence: 99%